Ultrasonic-assisted eggshell extract-mediated polymorphic transformation of calcium carbonate - SAYAN, PERVİZ; POLAT, SEVGİ (ELSEVIER, 2020)
This study aimed to evaluate the combined effects of eggshell extract and ultrasonic irradiation on the polymorphic transformation of calcium carbonate (CaCO3). In this context, XRD, Raman spectroscopy, SEM, AFM, TGA-FTIR, BET, and zeta potential analysis were used to identify and characterize the different polymorphs of CaCO3 obtained in the absence and presence of eggshell extract in the media with and without ultrasonic irradiation. The morphology and polymorphic nature of the CaCO3 crystals were observed to change, which indicated that the eggshell extract and ultrasonication influenced the structure and crystallization of CaCO3. The structural analysis results indicated that the addition of eggshell extract to the media resulted in the full transformation of calcite to the vaterite polymorph. The results also showed that ultrasonic irradiation had a more significant influence on the BET specific surface area of the crystals compared to the eggshell extract media. Furthermore, a Box-Behnken design with response surface methodology was employed to determine the optimal operating conditions for CaCO3 crystallization. The effects of stirring rate, extract concentration, and ultrasonic power on the BET surface area were investigated. The results show that the data sufficiently fit the second-order polynomial model. Understanding the eggshell extract-mediated polymorphic transformation with ultrasonic irradiation obtained in this study makes it possible to control the polymorphic formation and modify the product characteristics.
Keywords: Calcium carbonate; Ultrasonic irradiation; Eggshell extract; Box-Behnken design, Polymorphs; Vaterite; VATERITE PARTICLES; PRECIPITATION; CRYSTALLIZATION; MINERALIZATION; MICROPARTICLES; GROWTH